نوعية حياة مريضات سرطان الثدي خلال فترة المعالجة الكيماوية - غزال سوسن; نعمان مفيدة (Latakia University Journal -Medical Sciences Series, 2015)
مقدمة: يعاني مرضى السرطان من تغيرات كبيرة في حياتهم نتيجة التشخيص والمعالجة وسرعة تقدم المرض وكل ذلك يؤثر سلباً على نوعية حياتهم. الهدف: طبق البحث الحالي لاستقصاء نوعية حياة مريضات سرطان الثدي خلال فترة المعالجة الكيماوية في مستشفى تشرين الجامعي في اللاذقية. الطرائق: قامت 60 مريضة بملء استبيان نوعية الحياة للجمعية الأوربية لأبحاث ومعالجة السرطان المكون من 30 سؤال ونموذج (مديول)سرطان الثدي المكون من23 سؤال. النتائج: أظهرت النتائج أن 73.3% من المريضات تحت سن الخمسين ونصفهن لديه محصلة حالة صحية إجمالية أقل من 50 تعكس نوعية حياة متدنية مع اضطراب في الوظيفة الاجتماعية والنفسية بالإضافة إلى وظيفة الدور في الحياة. كما يعاني أكثر من67 % من المريضات من وجود أعراض مرتبطة بالمعالجة كان أهمها الغثيان والاقياء والزلة التنفسية وفقد الشهية والأرق والتعب أيضاً أظهرت النتائج تغير محصلة نوعية الحياة حسب العمر، والحالة الاجتماعية، والعمل دون تأثرها بتغير المستوى التعليمي ،أما بالنسبة لنموذج (مديول) سرطان الثدي أظهرت النتائج أن غالبية المريضات يعانين من تدني في الوظيفة الجنسية وانزعاج من فقد الشعر وأعراض الذراع لكن مع نظرة ايجابية راضية إلى المستقبل ،لم يظهر البحث وجود فروق ذات دلالة إحصائية في نوعية حياة بين مريضات مدينة اللاذقية ومريضات الريف وباقي المحافظات الأخرى. الاستنتاجات: يجب على مقدمي الرعاية الصحية وبشكل روتيني تقييم نوعية حياة مرضى السرطان خلال فترات المعالجة المختلفة للتأكد من تقديم الرعاية المناسبة والخدمات الداعمة لتحقيق ذلك لجميع المرضى. Background: people with cancer experience great changes in their life as a result of disease, treatment and disease prognosis which affect their quality of life .with the goal of investigating breast cancer patient’s quality of life during chemotherapy in Tishreen hospital in Latakia.. Methods: 60 patients were invited to complete the European organization of research and treatment quality of life questionnaire version 3 and breast cancer quality of life module during their early stage of chemotherapy. Results : the results show that the (73.3%) were under the age of fifty and half of them reported total health status score under (50) which reflects low quality of life in addition to impaired psychological ,social, cognitive and role functioning. Also more than 67% of patient suffered from chemotherapy- related side effects as nausea and vomiting, dyspnea, loss of appetite, insomnia, and fatigue. In addition to variance in quality of life scores according to age, marital status, occupation and level of education without changing of it by educational level. In addition to that the majority of patient had impaired sexual function and upset of hair loss and arm symptoms but with positive and optimistic future. perspective. No significant differences in quality of life scores were found between urban and rural patients. Conclusion. Health care provider should assess routinely cancer patient quality of life during treatment to ascertain of providing appropriate care with supportive services for all patients